1985
DOI: 10.1210/jcem-60-2-361
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Altered Prednisolone Kinetics in Patients with the Nephrotic Syndrome and in Women Taking Oral Contraceptive Steroids on Human Mixed Lymphocyte Cultures

Abstract: The purpose of this study was to examine the influence of altered prednisolone kinetics in patients with the nephrotic syndrome and women taking oral contraceptive steroids on mixed lymphocyte cultures (MLC). After oral and iv prednisolone treatment, blood samples were collected over 24 h. The area under the plasma concentration vs. time curve (AUC) of unbound, transcortin- bound, and albumin-bound prednisolone was determined. All plasma samples were incubated with MLCs, and the area under the inhibition vs. t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…In clinical practice one might have to initiate therapy with prednisone in patients who are already suffering from an infection or who are immunocompromised, conditions that might have precluded the participation in a controlled trial with prednisone. Furthermore, certain states, such as renal failure, hepatic disease, old age, or concomitant drug therapy (e.g., ketoconazole or oral contraceptive steroids), decrease the metabolism of prednisolone [95][96][97][98][99][100] and therefore might increase the likelihood of infections even at doses below the threshold doses for increased risk of infections found in the controlled trials. Conversely, Stuck, Minder, and Frey patients with an enhanced catabolism of the steroid because of induced microsomal liver enzymes by xenobiotics (mainly phenytoin, barbiturates, or rifampin) or because of hyperthyroidism exhibit less immunosuppressive effect -and as a corollary less infectious risk -from the same dose of prednisone than do patients with a normal steroid metabolism .…”
Section: Discussionmentioning
confidence: 99%
“…In clinical practice one might have to initiate therapy with prednisone in patients who are already suffering from an infection or who are immunocompromised, conditions that might have precluded the participation in a controlled trial with prednisone. Furthermore, certain states, such as renal failure, hepatic disease, old age, or concomitant drug therapy (e.g., ketoconazole or oral contraceptive steroids), decrease the metabolism of prednisolone [95][96][97][98][99][100] and therefore might increase the likelihood of infections even at doses below the threshold doses for increased risk of infections found in the controlled trials. Conversely, Stuck, Minder, and Frey patients with an enhanced catabolism of the steroid because of induced microsomal liver enzymes by xenobiotics (mainly phenytoin, barbiturates, or rifampin) or because of hyperthyroidism exhibit less immunosuppressive effect -and as a corollary less infectious risk -from the same dose of prednisone than do patients with a normal steroid metabolism .…”
Section: Discussionmentioning
confidence: 99%
“…U p until now, no significant relationship had been demonstrated between the plasma concentration of prednisolone and its therapeutic efficacy (Gambertoglio et al 1980). Furthermore, the biological effects cannot be derived directly from the measured concentrations of prednisolone in patients with the nephrotic syndrome for several reasons (Moothy et a1 1976;Rosner et a1 1982;Frey & Frey 1985). Therefore, prednisolone pharmacodynamics, such as those described in this study and those reported by others (Dumbleet a1 1983(Dumbleet a1 , 1986Lowyet a1 1984Lowyet a1 , 1985Langhoff et a1 1986), should be evaluated widely in renal transplant recipients and in patients with chronic renal failure awaiting renal transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…Madsbad et al for the first time cor· related the pharmacokinetic parameters of pred· nisone with galactose elimination capacity, an independen t quantitauve parameter of liver function. (4) When a 10-foid higher dose of prednisone (1 mg/kg) was given to patients wit h apparently normal li ver fun ction, no saturation of the conversion of prednisone to prc<inisolone was observed (Frey 8M et al 1985), an observation suggesting that In patients with ImpaIred hver function a low dose of pred. and that patie nts exhIbItIng a galactose eliminatIOn capaCity below 284 mg/mm had higher mean concentratIons of prcdmsone than predm.…”
Section: Ve R Diseasesmentioning
confidence: 99%